PESAN DAKWAH - Kamaluddin Kamaluddin (IAIN Padangsidimpuan, 2016)
Material message as one of the most important elements in da’wa activity needs to be managed effectively to achieve the expected goals. In addition to a deep mastery of the material, it needed accuracy in choosing the right kind of material for the situation faced mad'u. The selection of accurate materials, and appropriate techniques and steps in managing the message, must be based on some principles, namely the principles of relevance, consistency, adequacy and hierarchy based on kai'idah ushuliyah of message management. For a multicultural society such as Indonesia, da'wah of the message must necessarily be adapted to the philosophy of this nation. The diversity of ethnicity, culture, religion and language are sunnatullah. The message of da’wah that make every people in peace and good condition is the evidence of Muhammad's prophethood as rahmatan lil 'Alamin. Da'wah messages integrative be one means to deliver the Ummah tawhid civilization in all aspects of community life